2019
DOI: 10.3390/en12214022
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Nonlinear Wave-Loading Models on Rigid Cylinders in Regular Waves

Abstract: Monopiles able to support very large offshore wind turbines are slender structures susceptible to nonlinear resonant phenomena. With the aim to better understand and model the wave-loading on these structures in very steep waves where ringing occurs and the numerical wave-loading models tend to lose validity, this study investigates the distinct influences of nonlinearities in the wave kinematics and in the hydrodynamic loading models. Six wave kinematics from linear to fully nonlinear are modelled in combinat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…Additional simulations showed that instabilities only occurred for thin cylinders, that is, when the surface Keulegan-Carpenter number is moderate. When running the model without filtering and at sufficiently high-resolution, wave patterns similar to those identified by Swan and Sheikh 104 as type-2 waves appeared near the cylinder, which are nonlinear waves that would eventually break, and discussion of the physics has been considered by Mockute et al 105 for this type of problem. In order to investigate the stability question further, tests for kA = 0.05 and kR = 0.378 were conducted, without using any filtering of the free-surface.…”
Section: 51mentioning
confidence: 59%
“…Additional simulations showed that instabilities only occurred for thin cylinders, that is, when the surface Keulegan-Carpenter number is moderate. When running the model without filtering and at sufficiently high-resolution, wave patterns similar to those identified by Swan and Sheikh 104 as type-2 waves appeared near the cylinder, which are nonlinear waves that would eventually break, and discussion of the physics has been considered by Mockute et al 105 for this type of problem. In order to investigate the stability question further, tests for kA = 0.05 and kR = 0.378 were conducted, without using any filtering of the free-surface.…”
Section: 51mentioning
confidence: 59%
“…FD models neglect or approximate non-linear effects and are restricted to steady load conditions. Several important nonlinear and transient effects on fixed-bottom WTs have been observed in [28][29][30][31][32][33][34].…”
Section: Frequency Domain Modelmentioning
confidence: 99%
“…However, the OC3 Hywind test case provided by NREL includes all the hydrodynamic data obtained with the external software WAMIT [33]. More accurate models capable to account for important nonlinear effects, see for example [34][35][36][37][38][39] for fixed bottom platforms and [40][41][42][43] for floating platforms, should be used for higher fidelity simulations. However, when high efficiency is required as in the present case, the potential-flow theory together with the assumption of small waves and small body motion represent an acceptable trade-off between accuracy and efficiency.…”
Section: Hydrodynamic Modelmentioning
confidence: 99%